PEMANFAATAN YOUTUBE SEBAGAI MEDIA PEMBELAJARAN BAGI ANAK USIA DINI - Alfina Lailan (CV. ADIBA ASIHA AMIRA, 2022)
Currently, technology is experiencing rapid development that can be utilized by parents and educators as a learning tool, starting with the introduction of literacy and numeracy for early childhood. One of these is technology, namely YouTube. However, the use of this technology requires supervision, because behind the various advantages offered there are weaknesses. To support the effectiveness of its use in learning environments for children, educators need to have extensive knowledge so they are ready to make decisions about the right way to apply technology in the form of YouTube shows to meet the social, physical and cognitive needs of young children.